2008
DOI: 10.1007/s11064-008-9722-9
|View full text |Cite
|
Sign up to set email alerts
|

Wiring and Volume Transmission in Rat Amygdala. Implications for Fear and Anxiety

Abstract: The amygdala plays a key role in anxiety. Information from the environment reaches the amygdaloid basolateral nucleus and after its processing is relayed to the amygdaloid central nucleus where a proper anxiogenic response is implemented. Experimental evidence indicates that in this information transfer a GABAergic interface controls the trafficking of impulses between the two nuclei. Recent work indicates that interneuronal communication can take place by classical synaptic transmission (wiring transmission) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 162 publications
(296 reference statements)
2
20
0
Order By: Relevance
“…This suggestion is in line with a diminished open arm exploration observed in rats bred for high anxiety levels (Henninger et al 2000) or treated with anxiogenic compounds (Pellow et al 1985;Davis and Whalen 2001;Pérez de la Mora et al 2008Engin and Treit 2008). Moreover, the effects of the bilateral intra-amygdaloid administration of TPMPA on the exploration of the open arms of the maze do not seem to be secondary to changes in the general activity of the rats as neither the total number of entries into the open + closed arms of the maze, that is a built-in measure of locomotion in the elevated plus-maze (Pellow et al 1985), nor the locomotion in the open-field test was modified.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…This suggestion is in line with a diminished open arm exploration observed in rats bred for high anxiety levels (Henninger et al 2000) or treated with anxiogenic compounds (Pellow et al 1985;Davis and Whalen 2001;Pérez de la Mora et al 2008Engin and Treit 2008). Moreover, the effects of the bilateral intra-amygdaloid administration of TPMPA on the exploration of the open arms of the maze do not seem to be secondary to changes in the general activity of the rats as neither the total number of entries into the open + closed arms of the maze, that is a built-in measure of locomotion in the elevated plus-maze (Pellow et al 1985), nor the locomotion in the open-field test was modified.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, GABA A ρ1 receptors have been detected immunohistochemically in the posterior amygdala (Rosas-Arellano and Miledi, personal communication) and GABA A ρ2 receptors have been found by real-time polymerase chain reaction (RT-PCR) within the BLA and CeA (Esmaeili et al 2009). Furthermore, in line with these results, both the iontophoretic application of GABA to amygdala slices and the electrical stimulation of the medial intercalated paracapsular islands, which are clusters of GABAergic neurons that are interposed between the BLA and CeA and seem to control the flow of nerve impulses between these nuclei (Paré et al 2004;Pérez de la Mora et al 2008, were found to induce within the CeA inhibitory postsynaptic currents that were insensitive to bicuculline and partially blocked by the application of TPMPA (Delaney et al 1999(Delaney et al , 2001.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…The amygdala seems to be of paramount importance for the modulation of fear and anxiety (for reviews, see LeDoux, 2000;Everitt et al, 2003;Engin and Treit, 2008;Perez de la Mora et al, 2008). It comprises a number of nuclei, and an array of afferent, efferent, and interconnecting fibers (Nauta, 1962;Swanson and Petrovich, 1998;McDonald, 2003) occupying a large part of the mammalian medial temporal lobe.…”
Section: Introductionmentioning
confidence: 99%